CORRECTION - Agriculture, Economic of (Economics of Agriculture, 2018)
Jasmina Ćetković, Aleksandra Despotović, Miroslav Cimbaljević - Analyses of organization and milk production economics on farms in Montenegro (vol. 59, pg. 9, 2012). Summary: From the list of references of the above mentioned paper are deleted (by Correction) all quotes entered by mistake during the paper writing. Correction: From the above mentioned paper next incorrectly entered quotas are deleted from the list of references: 1. Bulatović, B., Despotović, A., Jovanović, M. (2000): Izbor optimalne strukture poljoprivredne proizvodnje sjevernog područja Crne Gore, Ekonomika poljoprivrede, br. 3- 4, str. 19-30, Beograd. 2. Drašković, B., Rajković, Z., Kostić, D. (2010): Proizvodnja mleka u Srbiji i položaj malih farmera, Ekonomika poljoprivrede, br. 4, str. 529-542, Beograd. 3. Vukelić, N., Novković, N. (2009): Ekonomski rezultati proizvodnje mleka na krupnim seljačkim gazdinstvima, Ekonomika poljoprivrede, br. 1, str. 99-110, Beograd. Mistakes are made by rough oversight during the paper writing. Mistakes are discovered during the creation of the Bibliometric report for the CEONs magazines for 2012. We thank to the team of CEON for the warning. Milutin Đorović, Simo Stevanović, Verica Lazić - The world and domestic markets for tobacco and tobacco products (vol. 59, pg. 21, 2012). Summary: From the list of references of the above mentioned paper are deleted (by Correction) all quotes entered by mistake during the paper writing. Correction: From the above mentioned paper next incorrectly entered quota is deleted from the list of references: 1. Zornic, B., et al. (2003): Tobacco Production in the Models of the Development of the Republics of Former Yugoslavia, Agricultural Economics, Ed. no. 1, Belgrade. Mistake is made by rough oversight during the paper writing. Mistake is discovered during the creation of the Bibliometric report for the CEONs magazines for 2012. We thank to the team of CEON for the warning.